2018
DOI: 10.1038/s41374-018-0025-8
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde accelerates wound healing by promoting angiogenesis via up-regulation of PI3K and MAPK signaling pathways

Abstract: The bark of Cinnamomum cassia (C. cassia) has been used for the management of coronary heart disease (CHD) and diabetes mellitus. C. cassia may target the vasculature, as it stimulates angiogenesis, promotes blood circulation and wound healing. However, the active components and working mechanisms of C. cassia are not fully elucidated. The Shexiang Baoxin pill (SBP), which consists of seven medicinal materials, including C. cassia etc., is widely used as a traditional Chinese patent medicine for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 55 publications
3
63
1
3
Order By: Relevance
“…9 Stem Cells International (Figure 7(b)) and mitogen-activated protein kinase (MAPK) (Figure 7(c)) showed the greatest difference between ADSC-Exo and HFF-Exo in promoting the survival of prefabricated skin flaps. Several studies [32,33] have reported that the PI3K-Akt and MAPK signaling pathways are closely related to wound vascularization. The differential miRNAs may thus enhance endothelial cell proliferation and motility and promote angiogenesis by activating the PI3K-Akt and MAPK signaling pathways.…”
Section: Mirna Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…9 Stem Cells International (Figure 7(b)) and mitogen-activated protein kinase (MAPK) (Figure 7(c)) showed the greatest difference between ADSC-Exo and HFF-Exo in promoting the survival of prefabricated skin flaps. Several studies [32,33] have reported that the PI3K-Akt and MAPK signaling pathways are closely related to wound vascularization. The differential miRNAs may thus enhance endothelial cell proliferation and motility and promote angiogenesis by activating the PI3K-Akt and MAPK signaling pathways.…”
Section: Mirna Expression Analysismentioning
confidence: 99%
“…According to KEGG analysis results, the target genes of the differential miRNAs were mainly enriched in the PI3K-Akt and MAPK pathways, and also in focal adhesion, Ras signaling, and vascular smooth muscle contraction pathways, which are closely related to cell proliferation and migration. Many studies [32,33] have shown that the activation of these pathways can significantly promote angiogenesis and promote wound repair. We therefore suggest that ADSC-Exo are affected by the ischemic environment, leading to the enrichment and activation of the differential miRNAs in the above pathways, and thus promoting vascularization of the prefabricated flaps.…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…A number of studies have shown that a combination of VEGFR and PDGFR with corresponding ligands can promote the proliferation and angiogenesis of vascular ECs by activating multiple signaling pathways, such as PI3K/ Akt, MAPK, and PLC-γ. 34,35 Therefore, GO can be used to stimulate the development of an immune microenvironment that is suitable for bone regeneration.…”
mentioning
confidence: 99%
“…Among the various signaling pathways involved in the regulation of DFUs, the MAPK signal transduction pathway is particularly important (24). The extracellular signal-related kinase (ERK) pathway is also considered to be an important MAPK signaling pathway, and has been revealed to have a crucial role in the inflammatory response induced by T cells by regulating the expression of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%